The acquisition of research skills through qualitative methods in the analysis of audio-visual narratives - Gutiérrez Leyton, Alma Elena; Torres Herrera, Moisés (COMMUNICATION. International Journal of Audiovisual Communication, Advertising and Cultural Studies, 2022)
Qualitative methods of research have in recent years-establish itself as a strategy, assertive and successful in the higher education system to link university students with the study of social phenomena from different disciplinary approaches. In the area of communication and specifically in the study of visual narratives, this paradigm, as embodied in the use of methods and tools, has enabled undergraduate and graduate students reconstruct reality from new interpretations of various social phenomena often they are outside its original context, such as poverty, inequality and violence, whether in the study of fiction programs or news. Through its approach to the world of research from the phenomenological paradigm, these researchers in training and upper middle class, encourage commitment and social awareness. This paper presents the results achieved by the authors for fourteen sixmonth periods as professors of three courses of Qualitative Research Methods: a professional level, and two graduate programs at a private university in northeastern Mexico. Notable in this descriptive analysis the methodological structure is based on courses, research skills acquired by students-translated master’s thesis and publications in national and international conferences and journals. Are sampled the work through methodological framework in which the courses were based, research skills acquired by students, master’s theses translated and published in national and international journals. Sample is taken as the work through methodologies such as qualitative content analysis, focus groups, ethnography and life stories, through techniques such as observation and in-depth interview.